Digital integral proportional controller for DC motors - Nazlıbilek, Sedat. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1984., 1984)
The object of this thesis is to analyse and design a microprocessor based digital speed control system for a d.c. motor system with an IP (Integral-Proportional) control algorithm. Also, the PI and the IP control systems are analysed using Laplace transforms and·z-transforms in the case of analog and discrete cases respectively. They are compared according to speed control accuracy, stability, and especially load characteristics. , The experimental set-up comprises a dc motor driven by a three-phase fully controlled bridge. The firing angle of the bridge is directly controlled, by the microcomputer. For the sensing of speed feedback signal, adc tachogenerator with a ten-bit A/D converter is utilised. The equations of the system are derived in discrete form and by use of them, it is shown that IP control result in a better performance than that of the PI control especially with respect to changes in the load torque.
Keywords: Electric motors, Direct current.